Extracellular vesicles from human plasma dampen inflammation and promote tissue repair functions in macrophages - Alan M. Adamczyk; María Luz Leicaj; Martina Paula Fabiano; Gonzalo Cabrerizo; Nadia Bannoud; Diego O. Croci; Kenneth W. Witwer; Federico Remes Lenicov; Matías Ostrowski; Paula Soledad Pérez (Journal of Extracellular Vesicles, 2023)
Abstract Although inflammation is a vital defence response to infection, if left uncontrolled, it can lead to pathology. Macrophages are critical players both in driving the inflammatory response and in the subsequent events required for restoring tissue homeostasis. Extracellular vesicles (EVs) are membrane‐enclosed structures released by cells that mediate intercellular communication and are present in all biological fluids, including blood. Herein, we show that extracellular vesicles from plasma (pEVs) play a relevant role in the control of inflammation by counteracting PAMP‐induced macrophage activation. Indeed, pEV‐treatment of macrophages simultaneously with or prior to PAMP exposure reduced the secretion of pro‐inflammatory IL‐6 and TNF‐α and increased IL‐10 response. This anti‐inflammatory activity was associated with the promotion of tissue‐repair functions in macrophages, characterized by augmented efferocytosis and pro‐angiogenic capacity, and increased expression of VEGFa, CD300e, RGS2 and CD93, genes involved in cell growth and tissue remodelling. We also show that simultaneous stimulation of macrophages with a PAMP and pEVs promoted COX2 expression and CREB phosphorylation as well as the accumulation of higher concentrations of PGE2 in cell culture supernatants. Remarkably, the anti‐inflammatory activity of pEVs was abolished if cells were treated with a pharmacological inhibitor of COX2, indicating that pEV‐mediated induction of COX2 is critical for the pEV‐mediated inhibition of inflammation. Finally, we show that pEVs added to monocytes prior to their M‐CSF‐induced differentiation to macrophages increased efferocytosis and diminished pro‐inflammatory cytokine responses to PAMP stimulation. In conclusion, our results suggest that pEVs are endogenous homeostatic modulators of macrophages, activating the PGE2/CREB pathway, decreasing the production of inflammatory cytokines and promoting tissue repair functions.